(untitled) (Environment & Health, 2022)
Target. From the standpoint of public health, analyze scientific literature data and terminology related to various hypostases / manifestations of malady. Materials and methods. The analysis of domestic and foreign publications devoted to terminological issues of assessing various aspects of the incidence of the population. Results. The state of research concerning various aspects of the concept of "disorder" in the scientific domestic and foreign literature has been determined. A review of the scientific literature revealed a lack of theoretical provisions on this topic that could be generalized, compared and contrasted. In everyday English, the use of concepts to describe malady (disease, illness, sickness, etc.) is often seen as arbitrary, and in the scientific field, they are the subject of professional discussions. For Ukraine, the analysis of malady terminology is new. The designation of the space for the use of certain terms is important, since the study of various aspects of the malady involves the use of various methods of collecting information, interpreting the data obtained, conclusions about ways to overcome disorders, etc. The definition of malady is not only a theoretical issue: it is important for medicine, social policy and the health care system in general. For public health, which is the most socially oriented branch of medicine, it is extremely important to take into account not only the purely biomedical (disease), but also the social (sickness) aspects of the disorders, as well as its self-esteem (illness).The combination and interrelation of various hypostases of the disorders included in the Twaddle triad is considered, a comparative analysis of its components has been carried out. The relevance of the analysis of the morbidity of the population and the justification of the most effective health-improving measures determines the advisability of taking into account various hypostases of ill health, and given the multidisciplinary nature of public health, the involvement of specialists in various fields.